Aldosterone Antagonists for Preventing the Progression of Chronic Kidney Disease: A Systematic Review and Meta-analysis - Navaneethan, Sankar D. (American Society of Nephrology, 2009)
Background and objectives: Addition of aldosterone antagonists (AA) might provide renal benefits to proteinuric chronic kidney disease (CKD) patients over and above the inhibition of renin-angiotensin system blockers (RAS). We evaluated the benefits and harms of adding selective and nonselective AA in CKD patients already on RAS. Design, setting, participants, & measurements: MEDLINE, EMBASE, and Renal Health Library were searched for relevant randomized clinical trials in adult CKD patients. Results were summarized using the random-effects model. Results: Eleven trials (991 patients) were included. In comparison to angiotensin- converting enzyme inhibitors (ACEi) and/or angiotensin receptor blockers (ARB) plus placebo, nonselective AA along with ACEi and/or ARB significantly reduced 24 h proteinuria (seven trials, 372 patients, weighted mean difference [WMD] −0.80 g, 95% CI −1.27, −0.33) and BP. This did not translate into an improvement in GFR (WMD −0.70 ml/min/1.73m(2), 95% CI −4.73, 3.34). There was a significant increase in the risk of hyperkalemia with the addition of nonselective AA to ACEi and/or ARB (relative risk 3.06, 95% CI 1.26, 7.41). In two trials, addition of selective AA to ACEi resulted in an additional reduction in 24 h proteinuria, without any impact on BP and renal function. Data on cardiovascular outcomes, long-term renal outcomes and mortality were not available in any of the trials. Conclusions: Aldosterone antagonists reduce proteinuria in CKD patients already on ACEis and ARBs but increase the risk of hyperkalemia. Long-term effects of these agents on renal outcomes, mortality, and safety need to be established.